The Correlation between Nicotine Dependence Level and Negative Symptom in Schizophrenic Patients at Psychiatric Department of PTPN XI Djatiroto Lumajang Hospital - Nafiys Hilmy; Alif Mardijana; Dwita Aryadina Rachmawati (Journal of Agromedicine and Medical Sciences, 2018)
Smoking behavior is one problem in schizophrenic patients. The prevalence of smoking in schizophrenic patients is reported 2-4 times greater than the normal population. Nicotine can induce the dopamine release so it increase positive symptom and improve negative symptom also cognitive deficits. These effects are an attempt by schizophrenic patients to reduce the side effects of antipsychotic drugs. This causes the need of increased antipsychotic doses. This study aims to determine the correlation between nicotine dependence level andnegative symptom in Schizophrenic Patients at Psychiatric Department, PTPN XI Djatiroto Hospital Lumajang. This is an analytical observational study with cross sectional study design which uses 30 patients with schizophrenia at Psychiatric Department, PTPN XI Djatiroto Hospital Lumajang who met inclusion and exclusion criteria. Nicotine dependence level and negative symptom were obtained with guided interview based on Fagerström Nicotine Dependence (FTND) questionnaire and score of Positive and Negative Syndrome Scale (PANSS) negative subscale. Spearman correlation test result between these variables is p=0,019 and r=0,426 which means there is significant correlation with moderate strength between nicotine dependence level and negative symptom in Schizophrenic patients at Psychiatric Department, PTPN XI Djatiroto Hospital Lumajang. Keywords: Schizophrenia, Negative Symptom, Nicotine Dependence